The Value and Assurance Factors in Tourists' Culinary Visit: Application of Involvement Theory - Amelya Sandra, Shinta; Arifin, Zainul; Rahimah, Anni (Profit: Jurnal Adminsitrasi Bisnis, 2023)
During the transition of tourism activity from the early pandemic to the post-pandemic period, the amount of domestic travel by tourists is gradually increasing. Tourists are presumed to be more concerned with the value and assurance aspects of their culinary visits to the travel destination. This study utilized the involvement theory model to analyze the effect of value and assurance as the antecedents to tourist involvement while simultaneously predicting the impact of tourist involvement on variety-seeking behaviour. The role of knowledge in moderating the relationship between value and assurance of tourist involvement is also presented. Structural path modelling was designed to explore the causal relationships among variables. An online survey was distributed to 200 local tourists who have travelled to Medan, North Sumatra, Indonesia. This study revealed the significant results of value and assurance in influencing tourist involvement positively, and so did tourist involvement in variety seeking. Research also extended previous studies that addressed the moderating role of knowledge in creating involvement. Knowledge only served a slight effect on the involvement relationship. However, managerial actors in the culinary business still need to focus on maintaining the availability of information to consumers, especially in the value and assurance aspect.